Financial analysis of the LEO Express a.s. company - Matveeva, Daria; Scholleová, Hana, 1964-; Dašková, Viktorie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
This bachelor's thesis deals with a financial analysis of the LEO Express a.s. company from the view of an external analyst for the period of business years 2011--2013. LEO Express is one or the first privately-owned passenger railway operators in the Czech Republic. This company entered on the route from Prague to Ostrava in year 2012 and contributed to the improvement of travelling culture. The thesis is split into three main parts. The methodical part defines the terminology and used indicators. The second part describes the area of business of LEO Express a.s. and identifies analysed competitors. The third most important part contains financial analysis of the company and further perspectives on the railway market. Apart from the thesis reveals strengths of company and possibilities where it can develop them further.
Vedoucí práce: Hana Scholleová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: ekonomika predprijatija i menedžment [obor bakal. práce]; bakalářské práce; bachelor's theses